Extracellular matrix and integrins influence in the regulation of myogenic precursor cells behaviour - Vaz, Raquel Rodrigues (2009)
Tese de mestrado, Biologia (Biologia Molecular Humana), 2009, Universidade de Lisboa, Faculdade de Ciências